11(2b-1)-(3b-7)=1

Simple and best practice solution for 11(2b-1)-(3b-7)=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11(2b-1)-(3b-7)=1 equation:


Simplifying
11(2b + -1) + -1(3b + -7) = 1

Reorder the terms:
11(-1 + 2b) + -1(3b + -7) = 1
(-1 * 11 + 2b * 11) + -1(3b + -7) = 1
(-11 + 22b) + -1(3b + -7) = 1

Reorder the terms:
-11 + 22b + -1(-7 + 3b) = 1
-11 + 22b + (-7 * -1 + 3b * -1) = 1
-11 + 22b + (7 + -3b) = 1

Reorder the terms:
-11 + 7 + 22b + -3b = 1

Combine like terms: -11 + 7 = -4
-4 + 22b + -3b = 1

Combine like terms: 22b + -3b = 19b
-4 + 19b = 1

Solving
-4 + 19b = 1

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + 19b = 1 + 4

Combine like terms: -4 + 4 = 0
0 + 19b = 1 + 4
19b = 1 + 4

Combine like terms: 1 + 4 = 5
19b = 5

Divide each side by '19'.
b = 0.2631578947

Simplifying
b = 0.2631578947

See similar equations:

| 5(x-2)=7x-16 | | dy/y^2=x | | (8x-9)(x-7)= | | ln(4y)=x | | -1/4(12-8x)-2x=3 | | 4senx+3cosx=3 | | -2x=-3y-5 | | xy+5y=3 | | -7x+17=-3x+1 | | x+11=-3x-9 | | 2(5x-3)=4x-18 | | -26=4(3x-3)-2 | | 2(x+1)+5=5x+19 | | -4x+34=4(2x-3)-2 | | 9x-5=6x-26 | | 22x(3x+4)=484 | | (2x^2)+34x+144=0 | | 4N+13=57 | | 8y-12=30 | | 4x^2+128=0 | | 6.55a+2.2b=1440 | | -3x-6=3x-60 | | (14x)+180=7000 | | (14x)+(142)=7000 | | 3x+16=5(x+4)+2 | | (x+iy)(1-i)+(2x+3iy)(1+i)=7 | | -6=3(3x+1)+9 | | Mm/ow= | | -3x-5=-x-29 | | 7x^2+24x^2=22500 | | (M*n)/(p*q) | | m/7-1=11 |

Equations solver categories